Clinical Trial Design—A Review—With Emphasis on Acute Intervertebral Disc Herniation - Jeffery, Nick D.; Olby, Natasha J.; Moore, Sarah A.; , The Canine Spinal Cord Injury Consortium (CANSORT-SCI); Moore, Sarah A.; Olby, Natasha J.; Gjessing, Kady M.; Davidson, Rhanna M.; Levine, Jonathan M.; McWhorter, Helen; Lewis, Melissa J.; Jeffery, Nick D.; et al. (Frontiers in Veterinary Science, 2020)
There is a clear need for new methods of treatment of acute disc herniation in dogs, most obviously to address the permanent loss of function that can arise because of the associated spinal cord injury. Clinical trials form the optimal method to introduce new therapies into everyday clinical practice because they are a reliable source of unbiased evidence of effectiveness. Although many designs are available, parallel cohort trials are most widely applicable to acute disc herniation in dogs. In this review another key trial design decision – that between pragmatic and explanatory approaches - is highlighted and used as a theme to illustrate the close relationship between trial objective and design. Acute disc herniation, and acute spinal cord injury, is common in dogs and there is a multitude of candidate interventions that could be trialled. Most current obstacles to large-scale clinical trials in dogs can be overcome by collaboration and cooperation amongst interested veterinarians.